NFLUENCE OF CYP4F2*3 ON RESPONSE TO CLOPIDOGREL IN PATIENTS WITH ACUTE CORONARY SYNDROME - K. B. Mirzaev; O. D. Konova; E. A. Grishina; K. A. Ryzhikova; Zh. A. Sozaeva; D. A. Andreev; M. Y. Gilyarov; D. A. Sychev (Рациональная фармакотерапия в кардиологии, 2018)
Background. Carriership of CYP4F2*3 (rs2108622, Val433Met) allelic variant can affect antiplatelet effect of clopidogrel, thus changing efficacy and safety of its standard dose.Aim. To study the impact of carriership of at least one CYP4F2*3 allele on the risk of resistance to clopidogrel in patients with acute coronary syndrome (ACS) who underwent percutaneous coronary intervention (PCI).Material and methods. The study enrolled 81 patients with ACS and PCI: 64 males and 17 females, mean age 63.9±10.9 years. CYP4F2 allelic variants were detected by the method of real-time polymerase chain reaction. Platelet functional activity was evaluated by a portative aggregometer – the VerifyNow P2Y12 assay.Results. Pharmacogenetic testing showed that 40 (49.4%) of ACS patients had normal genotype (CC), 38 (46.9%) patients were carriers of one associated with reduced drug metabolism allele (CT genotype), and 3 (3.7%) patients were homozygotes for T (TT genotype). Genotype and allele distribution was in the Hardy-Weinberg equilibrium (c2=2.79; p=0.095). There were no statistically significant differences in CYP4F2*3 allele frequency between patients that are resistant to clopidogrel (PRU>208) and in patients with a normal response to clopidogrel (PRU<208): 36.8% vs 54.8% (р=0.17). Average platelet reactivity units (PRU) and average platelet inhibition (%) in patients with and without T allelic variant of CYP4F2 also were not significantly different: 165.34±51.03 PRU vs 174.8±51.06 PRU (p=0.407), respectively, and 29.51±21.59% vs 27.72±18.35%, respectively (p=0.69).Conclusion. Carriership of CYP4F2*3 allelic variant does not affect antiplatelet effect of clopidogrel in ACS patients. Further research on larger samples is needed to determine the role of CYP4F2 polymorphisms in personalization of clopidogrel antiplatelet therapy.